Ginkgo biloba extract protects against mercury(II)-induced oxidative tissue damage in rats - VELİOĞLU ÖĞÜNÇ, AYLİZ; BECEREN, AYFER; ŞENER, GÖKSEL (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
Mercury(II) is a highly toxic metal which induces oxidative stress in the body. In this study we aimed to investigate the possible protective effect of Ginkgo biloba (EGb), an antioxidant agent, against experimental mercury toxicity in rat model. Following a single dose of 5 mg/kg mercuric chloride (HgCl2; Hg group) either saline or EGb (150 mg/kg) was administered for 5 days. After decapitation of the rats trunk blood was obtained and the tissue samples from the brain, lung, liver, and kidney were taken for the determination of malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO) activity and collagen contents. Formation of reactive oxygen species in the tissue samples was monitored by chemiluminescence (CL) technique. BUN, creatinin, ALT, and AST levels and tumor necrosis factor-alpha (TNF-alpha) and lactate dehydrogenase (LDH) activity were assayed in serum samples. The results revealed that HgCl2 induced oxidative damage Caused significant decrease in GSH level, significant increase in MDA level, MPO activity and collagen content of the tissues. Treatment of rats with EGb significantly increased the GSH level and decreased the MDA level, MPO activity, and collagen contents. Similarly, serum ALT, AST and BUN levels, as well as LDH and TNF-alpha, were elevated in the Hg group as compared to control group. On the other hand, EGb treatment reversed all these biochemical indices. Our results implicate that mercury-induced oxidative damage in brain, lung, liver, and kidney tissues protected by G. biloba extract, with its antioxidant effects. (c) 2006 Published by Elsevier Ltd.
Keywords: mercury chloride; Ginkgo biloba; lipid peroxidation; TNF-alpha; LIPID-PEROXIDATION; NITRIC-OXIDE; EGB 761; REACTIVE OXYGEN; IN-VIVO; MERCURY; STRESS; MELATONIN; KIDNEY; MYELOPEROXIDASE